ANALYZING THE GERUNDS USED IN THE WALT DISNEY FILMS - Ayu Novitasari Damayanti (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
This paper attempts to analyze the gerunds used in the Walt Disney films. The gerund is known as a part of Corpus Linguistics. Many uses of the gerund can be applied, especially that can be found in conversations of Walt Disney Films. The objective of the study is to reveal the common gerunds for conversations. The analysis is using a qualitative method based on the total of gerunds and the rank of words. The data consists of 2523 gerunds from several Walt Disney films such as Moana, Zootopia, Frozen, Tangled, Lion King, Toy Story, and Ice Ages. This is perhaps the most complex and arguable question that has risen among linguists about corpus linguistics: how many frequencies use gerunds? The gerund is so common. Finally, this paper highlights the gerunds tend to dominate a conversation of Walt Disney Films.